IMF Survey : Volume 29, Issue 22. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2000)
Following are edited excerpts from IMF Managing Director Horst Kohler's remarks, as prepared for delivery at the conference 'Completing Transition: The Main Challenges,' held in Vienna, Austria, on November 6. The full text is available on the IMF's website (www.imf.org).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet